Differences between Pinus pinea and Pinus pinaster as bioindicators of polycyclic aromatic hydrocarbons - Nuno Ratola (2011)
The potential of Univariate and Multivariate Analysis and specifically Principal Components Analysis (PCA), has been employed to assess the performance of pine needles as bioindicators of polycyclic aromatic hydrocarbons (PAHs) and particularly emphasize the crucial importance of making a distinction between different pine species if more than one is sampled. Four sampling sessions were done in 29 sites and needles of two common pine species (Pinus pinaster Ait. in 19 sites and Pinus pinea L in 12) were collected and analysed using gas chromatography-mass spectrometry (GC-MS) and PCA. The results obtained indicated significant differences between species, attributed to their different morphology. The mean total PAH concentration of the P. pinaster needles are over two times higher than P. pinea's. This difference is lower when the results are presented in lipid weight, but still statistically significant. Samples from the two sites with adjacent trees reinforce these conclusions, showing significant differences in terms of PAH mean concentration and aromatic ring patterns.